2021
DOI: 10.3389/fncel.2021.727336
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Spike Timing-Dependent Plasticity

Abstract: Since its discovery, spike timing-dependent synaptic plasticity (STDP) has been thought to be a primary mechanism underlying the brain’s ability to learn and to form new memories. However, despite the enormous interest in both the experimental and theoretical neuroscience communities in activity-dependent plasticity, it is still unclear whether plasticity rules inferred from in vitro experiments apply to in vivo conditions. Among the multiple reasons why plasticity rules in vivo might differ significantly from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 106 publications
0
25
0
Order By: Relevance
“…Next, we wanted to examine whether the spike-based LPL rule is consistent with experimental observations of plasticity induction. Experiments commonly report intertwined rate and spiketiming dependence presumably mediated through nonlinear voltage- and calcium-dependent cellular mechanisms [28, 29, 47]. Theoretical work has further established conceptual links between phenomenological STDP models, SFA, and BCM theory [20, 4852].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we wanted to examine whether the spike-based LPL rule is consistent with experimental observations of plasticity induction. Experiments commonly report intertwined rate and spiketiming dependence presumably mediated through nonlinear voltage- and calcium-dependent cellular mechanisms [28, 29, 47]. Theoretical work has further established conceptual links between phenomenological STDP models, SFA, and BCM theory [20, 4852].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, LPL qualitatively captures key phenomena observed in experiments such as STDP, the rate-dependence of plasticity, and metaplasticity, despite not being optimized to reproduce these phenomena. Rather our model offers a simple normative explanation for the necessity of different plasticity patterns that are also observed experimentally [47].…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of synaptic response in the “awake” ionic environment result in counterintuitive synaptic processing outcomes. The reduced Ca 2+ would be expected to decrease synaptic release ( Dodge and Rahamimoff, 1967 ) and does disrupt NMDAR-dependent synaptic plasticity in hippocampal slices ( Inglebert et al, 2020 ; Inglebert and Debanne, 2021 ). Although physiological ionic concentrations lead to decreased EPSP magnitudes, the NMDAR component amplified the response ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the amount of calcium entry per se is not the only variable determining the degree of potentiation. The kinetics and source of calcium entry may also influence potentiation ( Inglebert and Debanne, 2021 ; Zhou et al, 2005 ), as well as possible involvement of neuromodulators. See, for example, Gordon et al, 2006 , where we showed that in distal basal dendrites of layer 2–3 neocortical pyramidal neurons, brain-derived neurotrophic factor (BDNF) was a necessary requirement to gate plasticity in addition to calcium entry.…”
Section: Discussionmentioning
confidence: 99%